2016
DOI: 10.1039/c6fo00731g
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-independent identification of bovine milk-derived peptides in breast-milk

Abstract: Exclusively breast-fed infants can exhibit clear signs of IgE or non IgE-mediated cow's milk allergy. However, the definite characterization of dietary cow's milk proteins (CMP) that survive the maternal digestive tract to be absorbed into the bloodstream and secreted into breast milk remains missing. Herein, we aimed at assessing possible CMP-derived peptides in breast milk. Using high performance liquid chromatography (HPLC)-high resolution mass spectrometry (MS), we compared the peptide fraction of breast m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 44 publications
(59 reference statements)
3
21
1
Order By: Relevance
“…On average, more than 1,200 peptides derived from endogenous proteins were identified by HPLC-MS/MS in the 12% TCA-soluble peptide fraction of each breast milk sample (not shown), as already reported in our previous work ( 24 ). However, the repertory of the endogenous peptides exhibited a significant intra-individual variability, as clearly observed when comparing the chromatographic profiles.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…On average, more than 1,200 peptides derived from endogenous proteins were identified by HPLC-MS/MS in the 12% TCA-soluble peptide fraction of each breast milk sample (not shown), as already reported in our previous work ( 24 ). However, the repertory of the endogenous peptides exhibited a significant intra-individual variability, as clearly observed when comparing the chromatographic profiles.…”
Section: Resultssupporting
confidence: 85%
“…For the first time, we exploited MS to detect peptides arising from the digestion of bovine casein and whey proteins excreted into the breast milk of lactating donors after an oral administration of cow's milk ( 24 ). In particular, bovine β-Lg and α s1 -casein fragments were detected in the 12% trichloroacetic (TCA)-soluble fraction of two and one out six breast milk samples, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Our study provides strong evidence for the presence of intact nonhuman proteins in human milk, from mothers not exposed to any dietary intervention. Notably, there was an earlier study 23 wherein they identiified the YVEELKPTPEGDL peptide from bovine Beta-lactoglobulin in human milk. We additionally searched raw files of previously published human milk proteomics studies deposited in PRIDE 38 (PXD00365 and PXD00296) using our search parameters and identified quite a few nonhuman tryptic peptides, mostly originating from bovine milk proteins (e.g., “HIQKEDVPSER” and “FFVAPFPEVFGK” from bovine Alpha-S1-casein, “YLGYLEQLLR” from bovine or sheep Alpha-S1-casein, “AVPYPQR” from bovine Beta-casein, “VLPVPQK” from bovine or sheep Beta-casein, “YIPIQYVLSR” from bovine or sheep Kappa-casein) that were also identified in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively high levels of BLG peptide sequences that we found in milk from allergic mothers explains the high sequence coverage of BLG in the current study when compared to Zhu et al [2]. Because we removed small peptides by filter-aided sample preparation (10-20 kDa cutoff), no comparison could be made with previous peptidomics studies [3,4]. Other qualitative differences with these previous studies can be attributed to the more strict filtering on false positives that we applied, the inclusion of serum albumins, the inclusion of semi-trypsin and non-trypsin-digested sequences, and to the inclusion of milk from allergic mothers.…”
Section: Discussionmentioning
confidence: 52%
“…According to studies using mass spectrometry, the main biological source of the nonhuman proteinaceous molecules in human milk seems to be bovine milk. A peptidomics study demonstrated the presence of two peptides originating from bovine β-lactoglobulin (BLG) and one originating from α S1 -casein [3]. In a later study, this was extended with peptides from α-lactalbumin (ALA), κ-casein, β-casein, and lactoferrin [4].…”
Section: Introductionmentioning
confidence: 97%